Correlates of prior HIV testing and schistosomiasis treatment: Baseline survey findings from the "creating demand for fishermen's schistosomiasis HIV services" (FISH) cluster-randomized trial in Mangochi, Malawi. - Geoffrey Kangogo; Donaldson F Conserve; Sekeleghe Kayuni; Moses K Kumwenda; Kathryn L Dovel; James Chirombo; Peter MacPherson; Elizabeth L Corbett; Anthony Butterworth; Augustine Talumba Choko (PLoS Neglected Tropical Diseases)
Background Fishing exposes fishermen to schistosomiasis-infested fresh water and concurrently through precarious livelihoods to risky sexual behaviour, rendering these two infections occupational hazards for fishermen. This study aimed to characterize the knowledge of the two conditions to obtain necessary data for a subsequent cluster randomized trial designed to investigate demand creation strategies for joint HIV-schistosomiasis service provision in fishing villages on the shores of southern Lake Malawi. Methods Enumeration of all resident fishermen in 45 clusters (fishing communities) was carried out between November 2019 and February 2020. In a baseline survey, fishermen reported their knowledge, attitudes and practices in the uptake of HIV and schistosomiasis services. Knowledge of HIV status and previous receipt of praziquantel were modelled using random effects binomial regression, accounting for clustering. Prevalence of willingness to attend a beach clinic was computed. Results A total of 6,297 fishermen were surveyed from the 45 clusters with harmonic mean number of fishermen per cluster of 112 (95% CI: 97; 134). The mean age was 31.7y (SD: 11.9) and nearly 40% (2,474/6,297) could not read or write. Overall, 1,334/6,293 (21.2%) had never tested for HIV, with 64.4% (3,191/4,956) having tested in the last 12 months, and 5.9% (373/6290) taking antiretroviral therapy (ART). In adjusted analyses, being able to read and write (adjusted risk ratio [aRR: 1.91, 95% CI: 1.59-2.29, p<0.001); previous use of praziquantel (aRR: 2.00,95% CI: 1.73-2.30, p<0.001); knowing a relative or friend who died of HIV (aRR: 1.54,95% CI: 1.33-1.79, p<0.001); and being on ART (aRR: 12.93, 95% CI: 6.25-32.93, p<0.001) were associated with increased likelihood of ever testing for HIV. Only 40% (1,733/4,465) had received praziquantel in the last 12 months. Every additional year of age was associated with 1% decreased likelihood of having taken praziquantel in the last 12 months (aRR: 0.99, 95% CI: 0.98-0.99, p<0.001). However, recent HIV testing increased the likelihood of taking praziquantel by over 2-fold (aRR 2.24, 95% CI: 1.93-2.62, p<0.001). Willingness to attend a mobile beach clinic offering integrated HIV and schistosomiasis services was extremely high at 99.0% (6,224/6,284). Conclusion In a setting with an underlying high prevalence of both HIV and schistosomiasis, we found low knowledge of HIV status and low utilization of free schistosomiasis treatment. Among fishermen who accessed HIV services, there was a very high likelihood of taking praziquantel suggesting that integrated service delivery may lead to good coverage. Trial registration This trial is registered in the ISRCTN registry: ISRCTN14354324; date of registration: 05 October 2020.